2021
DOI: 10.1038/s41598-021-90663-z
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of resting-state network nodes preferentially propagates to structurally rather than functionally connected regions

Abstract: Combining Transcranial Magnetic Stimulation (TMS) with electroencephalography (EEG) offers the opportunity to study signal propagation dynamics at high temporal resolution in the human brain. TMS pulse induces a local effect which propagates across cortical networks engaging distant cortical and subcortical sites. However, the degree of propagation supported by the structural compared to functional connectome remains unclear. Clarifying this issue would help tailor TMS interventions to maximize target engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…In the case of TMS the direct physical and physiological effects at the primary stimulation site of an extracranially-applied magnetic perturbation are reasonably well-understood: secondary electrical currents initially depolarize the membranes of cells in the superficial neural tissue underneath the coil, causing action potentials and an associated local response in the stimulated brain region 21 . Concurrently, this local electrical activation propagates (as some combination of soma-originating and prodromic axon-originating action potentials) along white matter pathways to reach distant cortical and subcortical sites, resulting in predominantly excitatory effects with magnitudes depending on the strength of the anatomical connections 22 . The final EEG-measurable outcomes of this process appear as early (<100ms) and late (>100ms) responses at both the primary stimulation site and a broad set of interconnected brain regions, usually persisting for ∼300ms, and showing reliable characteristic patterns but also high levels of inter-subject variability 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of TMS the direct physical and physiological effects at the primary stimulation site of an extracranially-applied magnetic perturbation are reasonably well-understood: secondary electrical currents initially depolarize the membranes of cells in the superficial neural tissue underneath the coil, causing action potentials and an associated local response in the stimulated brain region 21 . Concurrently, this local electrical activation propagates (as some combination of soma-originating and prodromic axon-originating action potentials) along white matter pathways to reach distant cortical and subcortical sites, resulting in predominantly excitatory effects with magnitudes depending on the strength of the anatomical connections 22 . The final EEG-measurable outcomes of this process appear as early (<100ms) and late (>100ms) responses at both the primary stimulation site and a broad set of interconnected brain regions, usually persisting for ∼300ms, and showing reliable characteristic patterns but also high levels of inter-subject variability 23 .…”
Section: Introductionmentioning
confidence: 99%
“…There is growing awareness amongst neuroscientists that this hierarchical network structure of brain organization shapes the spatiotemporal propagation of activity evoked by brain stimulation 19,20,30 , and specifically that iES effects depend on the network connectivity profile of the region being stimulated [31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…There is growing awareness amongst neuroscientists that this hierarchical network structure of brain organization shapes the spatiotemporal propagation of activity evoked by brain stimulation 19,20,30 , and specifically that iES effects depend on the network connectivity profile of the region being stimulated 3135 . A seminal recent study reported that patients’ self-reported perception of iES stimulation intensity depend on the stimulated region’s position in the cortical hierarchy, with simpler effects in lower-level networks and more complex, heterogeneous effects in higher-order networks 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering studies have shown that TMS-evoked potentials (TEPs) represent the propagation of cortical responses from the stimulated area to the connected ones [4,5], conveying state-dependent information [6,7]. In recent years, a deeper understanding of the TMS-EEG signal was ensured by the integration with other neuroimaging techniques, such as the magnetic resonance, indicating that TMS signal propagates mainly on structural connections of the stimulated networks [8][9][10].…”
Section: Introductionmentioning
confidence: 99%